A Multi-model Air Quality System for Health Research: Road model development and evaluation. (September 2022) - Seaton, Martin; O'Neill, James; Bien, Brian; Hood, Christina; Jackson, Mark; Jackson, Rose; Johnson, Kate; Oades, Molly; Stidworthy, Amy; Stocker, Jenny; Carruthers, David
Abstract: Poor air quality impacts life expectancy and quality of life of populations worldwide. Numerical models generate comprehensive air pollutant concentration datasets, useful for quantifying historic, current and, through projections, future air pollution effects on health. However, it is challenging to accommodate the full range of dispersion and chemistry processes affecting both regional and local scales in a single model. The scientific formulation and evaluation of a new quasi-Gaussian road source dispersion model, ADMS-Local, is presented. This model has been developed as a component for the 'Multi-model Air Quality System for Health Research' (MAQS-Health). ADMS-Local accounts for the influence of urban morphology on dispersion, as well as near-road NOX chemistry processes, leading to the spatial resolution of pollutant concentration gradients occurring over distances of a few metres. The model is optimised for use within the MAQS-Health system, where local modelling for each regional model grid cell is run in parallel. Graphical abstract: Image 1 Highlights: Air quality datasets are required for respiratory disease health research. Street-scale air quality models can generate extensive pollutant datasets. ADMS-Local is a new road source dispersion model for use in MAQS-Health. ADMS-Local accounts for near-field NOx chemistry and street canyon dispersion. ADMS-Local has been evaluated in open road, street canyon and urban environments.